A Service-Oriented Cloud-Based Management System for the Internet-of-Drones - Koubâa, Anis (2017)
17th International Conference on Autonomous Robot Systems and Competitions (ICARSC 2017). 26 to 30, Apr, 2017. Coimbra, Portugal.